Pengaruh Menempel Serutan Pensil Terhadap Kemampuan Motorik Halus Anak di Taman Kanak-Kanak Kartika 1.61 Padang - Yeni, Indra; Sari, Ririn Novita (Jurnal Family Education, 2023)
This research is motivated by the development of children's fine motor skills that have not developed optimally, it can be seen that children are not able to coordinate hands and eyes when children are doing sticking activities. This study aims to prove the effect of sticking pencil shavings on fine motor skills of children in Kartika Kindergarten 1.61 Padang. This study uses a quantitative approach with a quasi-experimental design. The population of this study were all children at Kartika Kindergarten 1.61 Padang, while the sample for this study was class B1 as the experimental class and class B2 as the control class. Data collection techniques used tests in the form of statements of 4 statement items and data analysis techniques using normality tests, homogeneity tests, hypothesis tests with the help of computerized SPSS 25. The results of the study show that the significant value of the experimental class and control class is > 0.05 and is stated to be normally distributed, then the variance of the N-gain data for the experimental class and control class is the same or homogeneous. Based on the table above, it is known that the sig (2-tailed) value is 0.000 and stated <0.05. Thus it was concluded that there was an effect of sticking pencil shavings on fine motor skills of children in Kartika Kindergarten 1.61 Padang.